Nicotinamide Riboside: What It Takes to Incorporate It into RNA - Felix Wenzek; Alexander Biallas; Sabine Müller (Molecules, 2024)
Nicotinamide is an important functional compound and, in the form of nicotinamide adenine dinucleotide (NAD), is used as a co-factor by protein-based enzymes to catalyze redox reactions. In the context of the RNA world hypothesis, it is therefore reasonable to assume that ancestral ribozymes could have used co-factors such as NAD or its simpler analog nicotinamide riboside (NAR) to catalyze redox reactions. The only described example of such an engineered ribozyme uses a nicotinamide moiety bound to the ribozyme through non-covalent interactions. Covalent attachment of NAR to RNA could be advantageous, but the demonstration of such scenarios to date has suffered from the chemical instability of both NAR and its reduced form, NARH, making their use in oligonucleotide synthesis less straightforward. Here, we review the literature describing the chemical properties of the oxidized and reduced species of NAR, their synthesis, and previous attempts to incorporate either species into RNA. We discuss how to overcome the stability problem and succeed in generating RNA structures incorporating NAR.